2020
DOI: 10.1051/cocv/2020008
|View full text |Cite
|
Sign up to set email alerts
|

A global maximum principle for optimal control of general mean-field forward-backward stochastic systems with jumps

Abstract: The purpose of this paper is to explore the necessary conditions for optimality of meanfield forward-backward delay control systems. A new estimate is proved, which is a powerful tool to deal with the optimal control problems of mean-field type with delay. Different from the classical situation, in our case the first-order adjoint system is an anticipated mean-field backward stochastic differential equation, and the second-order adjoint system is a system of matrix-valued process, not mean-field type. With the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Combining the two aspects above with the partially observed feature, in this paper, we aim to study a global maximum principle for partially observed controlled forward-backward stochastic system with random jumps, where all the coefficients contain the control variable. We note that, very recently, Hao and Meng [6] obtained a global maximum principle for optimal control of the general mean-field forwardbackward stochastic system with jumps. However, the jump term in the SDEP of their paper does not contain the control variable and the cost functional is a special recursive case.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Combining the two aspects above with the partially observed feature, in this paper, we aim to study a global maximum principle for partially observed controlled forward-backward stochastic system with random jumps, where all the coefficients contain the control variable. We note that, very recently, Hao and Meng [6] obtained a global maximum principle for optimal control of the general mean-field forwardbackward stochastic system with jumps. However, the jump term in the SDEP of their paper does not contain the control variable and the cost functional is a special recursive case.…”
Section: Introductionmentioning
confidence: 93%
“…By introducing a state decomposition and backward separation approach, Wang et al [42] studied an linear-quadratic (LQ for short) stochastic control problem of FBSDEs, where the drift coefficient of the observation equation is linear with respect to state x, and the observation noise is correlated with the state noise. Some recent progress for partially observed problems, has been made in mean-field type controls (see [19], [44], [6]), differential games (see [45], [10], [51], [57], [63]), random jumps (see [20], [37], [52], [53], [54], [62]), time delay (see [16]) and applications in finance (see [56], [58]). The partially observed stochastic control problem is usually associated with the state filtering and estimation technique, and we only list some main references such as [18], [2], [55], [39], [54], [43], [34].…”
Section: Introductionmentioning
confidence: 99%
“…Using the classical variational analysis approach, Frankowska, Zhang & Zhang 5,6 derived the second‐order necessary optimality conditions for stochastic optimal controls under nonconvex control domain. Some representative works on the necessary optimality conditions in continuous‐time framework, to name a few, include References 7–17.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, global stochastic maximum principle for recursive utilities and fully coupled forward-backward stochastic differential equations (FBSDEs for short) were obtained in Hu [12] and Hu et al [13], respectively. Hao and Meng [10] proved a maximum principle of optimal control problem for a class of general mean-field forward-backward stochastic systems with jumps where the diffusion coefficients depend on control, but the coefficients of jump terms are independent of control. Song et al [32] obtained a maximum principle for progressive optimal control of SDEPs by introducing a new method of variation which is a correction of [33].…”
Section: Introductionmentioning
confidence: 99%